Nursing care mapping for patients at risk of falls in the Nursing Interventions Classification - Melissa de Freitas Luzia; Miriam de Abreu Almeida; Amália de Fátima Lucena (SciELO, 2014)
Objective: Identifying the prescribed nursing care for hospitalized patients at risk of falls and comparing them with the interventions of the Nursing Interventions Classifications (NIC). Method: A cross-sectional study carried out in a university hospital in southern Brazil. It was a retrospective data collection in the nursing records system. The sample consisted of 174 adult patients admitted to medical and surgical units with the Nursing Diagnosis of Risk for falls. The prescribed care were compared with the NIC interventions by the cross-mapping method. Results: The most prevalent care were the following: keeping the bed rails, guiding patients/family regarding the risks and prevention of falls, keeping the bell within reach of patients, and maintaining patients' belongings nearby, mapped in the interventions Environmental Management: safety and Fall Prevention. Conclusion: The treatment prescribed in clinical practice was corroborated by the NIC reference.